GENDER INEQUALITY IN UZBEKISTAN: PROBLEMS OF ACCESS TO JUSTICE FOR WOMEN AFFECTED BY DOMESTIC VIOLENCE (World Bulletin of Management and Law, 2023)
This article presents a legal analysis of existing problems in ensuring gender equality in the Republic of Uzbekistan. The article qualitatively and quantitatively analyzes the problem of domestic violence against women, which is one of the main factors causing gender inequality in society. The political, social, economic and cultural obstacles to the realization of the right and access to justice for women victims of domestic violence are considered in detail. In addition, based on official statistics provided by law enforcement agencies, a cross-analysis was made of the number of protection orders issued to women over the past year, and the number of decisions made by administrative and criminal courts in these types of cases. Based on the problems and shortcomings studied, proposals and recommendations were developed to eliminate domestic violence against women, which is one of the main factors causing gender inequality in Uzbekistan
Keywords: gender equality; domestic violence; justice; stereotypes